2013
DOI: 10.1016/j.tox.2012.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Ptaquiloside reduces NK cell activities by enhancing metallothionein expression, which is prevented by selenium

Abstract: Pteridium aquilinum, one of the most important poisonous plants in the world, is known to be carcinogenic to animals and humans. Moreover, our previous studies showed that the immunosuppressive effects of ptaquiloside, its main toxic agent, were prevented by selenium in mouse natural killer (NK) cells. We also verified that this immunosuppression facilitated development of cancer. Here, we performed gene expression microarray analysis in splenic NK cells from mice treated for 14 days with ptaquiloside (5.3 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…It is well known that PT can cause toxicity to the immune system, which could contribute to the activation of a latent and/or subclinical urothelial BPV-2 infection resulting in neoplasia [13]. PT is a powerful immune suppressor that is genotoxic for lymphocytes [11, 1517] and depresses NK cell activities [18]. …”
Section: Introductionmentioning
confidence: 99%
“…It is well known that PT can cause toxicity to the immune system, which could contribute to the activation of a latent and/or subclinical urothelial BPV-2 infection resulting in neoplasia [13]. PT is a powerful immune suppressor that is genotoxic for lymphocytes [11, 1517] and depresses NK cell activities [18]. …”
Section: Introductionmentioning
confidence: 99%
“…It was also verified that selenium supplementation prevents decrease in NK cytotoxicity which is caused by p. aquilinum (Latorre et al, 2011). In 2013 researchers showed that selenium prevents carcinogenic effects caused by immunosuppressive effects of bracken fern (Latorre et al, 2013). Furthermore, ptaquiloside involved in bracken may also promote carcinogenicity by decreasing immune supervision against lately arising tumors (Gil da Costa et al, 2012).…”
Section: Immunomodulatory Effects Of Bracken-fernmentioning
confidence: 97%
“…In fact, one single dose of bracken extracts induced both structural and numerical chromosome aberrations in Swiss mice (Almeida Santos et al ., ). Bracken also exhibits a significant immunosuppressive effect, reducing natural killer cells, which could undermine tumour surveillance (Latorre et al ., ).…”
Section: Carcinogenic Potential Of Fernsmentioning
confidence: 97%